A literatura brasileira: uma análise do preconceito racial no romance o mulato de Aluísio Azevedo - SOUSA, Lorena de Nazaré Silva de (2024)
The present work aims to present the racial prejudice present in the novel O Mulato by Aluísio Azevedo published in 1881, highlighting the protagonist Raimundo, who is the main target of prejudice due to his black origins. This work presents the social reality of the 19th century, a time when society was undergoing major advances and transformations. An approach to naturalism will be made, highlighting the main theories that emerged at that time, presenting the relationship between naturalism and science, and how a naturalist novel is characterized, based on the experimental novel, which was responsible for Zola, which was based on the models observation scientists. Next, the relationship between literature and society will be discussed, emphasizing its social importance and its ability to develop the critical being of human beings, as presented by Antônio Cândido, also focusing on the presence of black people in society and their representation in literature. Finally, we will present in the novel O Mulato how racial prejudice is manifested in the writing of the novel, emphasizing the characters, their lines and racist attitudes.